Fatigue crack propagation behavior of RC beams strengthened with CFRP under cyclic bending loads. Issue 1 (12th July 2017) - Li, Dongyang; Huang, Peiyan; Guo, Xinyan; Zheng, Xiaohong; Lin, Jiaxiang; Chen, Zhanbiao
Abstract: A fatigue crack propagation equation of reinforced concrete (RC) beams strengthened with a new type carbon fiber reinforced polymer was proposed in this paper on the basis of experimental and numerical methods. Fatigue crack propagation tests were performed to obtain the crack propagation rate of the strengthened RC beams. Digital image correlation method was used to capture the fatigue crack pattern. Finite element model of RC beam strengthened with carbon fiber reinforced polymer was established to determinate J ‐integral of a main crack considering material nonlinearities and degradation of material properties under cyclic loading. Paris law with a parameter of J ‐integral was developed on the basis of the fatigue tests and finite element analysis. This law was preliminarily verified, which can be applied for prediction of fatigue lives of the strengthened RC beams.